Metaphorical Framing in Political Discourse: A Longitudinal Study of Conceptual Metaphor Use in American Presidential Speeches - Hazim Eadan Salim (JALL (Journal of Applied Linguistics and Literacy), 2026)
While extensive studies exist on conceptual metaphors in political discourse, a comprehensive longitudinal analysis investigating how these conceptual metaphors endure and evolve across different American presidential administrations over time is lacking. Addressing this gap, this study tracks and analyzes the usage of conceptual metaphors related to ‘war’ and ‘national security’ across different presidential administrations. Drawing on the extensive literature in the field of conceptual metaphors in political discourse, this study presents a large-scale longitudinal analysis using Conceptual Metaphor Theory (Lakoff and Johnson, 1980) to examine eighteen pivotal presidential speeches (1941–2021), using mixed- methods approach that consists of quantitative corpus analysis (AntConc) and qualitative metaphor identification conducted according to the Metaphor Identification Procedure (MIP). Findings indicate that conceptual metaphors are not static, fixed rhetorical devices employed by the political actors in reference to stable specialized target domains; they appear to be dynamic instruments of rhetoric shaped by the historical and socio-political context in which they are used. This study is predominantly characterized by two complementary trends: on the one hand, a core set of conceptual metaphorical patterns persisted across the corpus, and on the other hand their source domains and specific metaphorical vehicles have undergone significant evolutionary processes. These changes are classified as lexical evolution (updating vehicles within a stable source domain) and conceptual evolution (re-assigning the target domain to a new source domain). One central observation is that it is naturalness itself, as a phenomenon of nature, that serves as the ubiquitous source domain for both war and national security as concepts. This study contributes a nuanced longitudinal perspective to the field, illustrating how political language maintains rhetorical stability while evolving to meet contemporary realities.